PENGOLAHAN DATA PENGARSIPAN KARTU AK-1 PADA DINAS TENAGA KERJA, KOPERASI DAN UKM (DISNAKERKOP) KOTA JAMBI BERBASIS WEB : Archiving, Data Flow Diagram (DFD), Data Processing, Waterfall, Web. - rahmawati, Noni; Sopian, Abu; -, Radhiallah; Huda Aminuddin, Fattachul; -, Riswan (LP2M Universitas Nurdin Hamzah, 2025)
Processing AK-1 Card archiving data is an important aspect of administration at the Jambi City Manpower, Cooperatives and SMEs Service (Disnakerkop). This study aims to design and implement a filing system that is efficient, accurate and easy to access. The method used in this research is the Waterfall method and data flow diagram (DFD). The application created from this research shows that a computer-based filing system can increase speed and accuracy in searching for AK-1 Card data, as well as reducing the risk of data loss. Implementation of this system can make a positive contribution to the performance of the Jambi City Department of Manpower, Cooperatives and SMEs (Disnakerkop) in managing workforce data. Keywords : Archiving, Data Flow Diagram (DFD), Data Processing, Waterfall, Web